2008
DOI: 10.1002/nme.2266
|View full text |Cite
|
Sign up to set email alerts
|

An implicit corrected SPH formulation for thermal diffusion with linear free surface boundary conditions

Abstract: SUMMARYThe smoothed particle hydrodynamics (SPH) method has proven useful for modeling large deformation of fluids including fluids with stress-free surfaces. Because of the Lagrangian nature of the method, it is well suited to address the thermal evolution of these free surface flows. Boundary conditions at the interface of the fluid with a solid wall are usually enforced through the use of boundary particles. However, applying conditions at free surfaces, in particular gradient boundary conditions, can be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 36 publications
2
93
0
Order By: Relevance
“…In their derivation, Jubelgas et al (2004) expanded a function into a Taylor series ignoring all thirdor higher-order terms. Following the same line, Schwaiger (2008) showed that…”
Section: Lp-sph01mentioning
confidence: 87%
See 4 more Smart Citations
“…In their derivation, Jubelgas et al (2004) expanded a function into a Taylor series ignoring all thirdor higher-order terms. Following the same line, Schwaiger (2008) showed that…”
Section: Lp-sph01mentioning
confidence: 87%
“…(14) will be the same as that given by Jubelgas et al (2004) and its discretized form will be LP-SPH03 with η = 0. Corresponding to his formulation, Schwaiger (2008) gave the following discrete Laplacian: LP-SPH04:…”
Section: Lp-sph01mentioning
confidence: 99%
See 3 more Smart Citations